2015
DOI: 10.4161/19420862.2014.985504
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of viscosity reducing mutants of a monoclonal antibody: Hydrophobic versus electrostatic inter-molecular interactions

Abstract: High viscosity of monoclonal antibody formulations at concentrations ≥100 mg/mL can impede their development as products suitable for subcutaneous delivery. The effects of hydrophobic and electrostatic intermolecular interactions on the solution behavior of MAB 1, which becomes unacceptably viscous at high concentrations, was studied by testing 5 single point mutants. The mutations were designed to reduce viscosity by disrupting either an aggregation prone region (APR), which also participates in 2 hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 48 publications
2
88
0
Order By: Relevance
“…This option requires an advanced understanding of sequencestructure properties of the drug candidates and access to protein engineering and molecular biology facilities. 75 …”
Section: Strategy II (Optimization Of Antibody Lead Candidate(s) For mentioning
confidence: 99%
See 3 more Smart Citations
“…This option requires an advanced understanding of sequencestructure properties of the drug candidates and access to protein engineering and molecular biology facilities. 75 …”
Section: Strategy II (Optimization Of Antibody Lead Candidate(s) For mentioning
confidence: 99%
“…Use of full-length antibody models may further improve accuracy of the viscosity prediction methods due to improved descriptions of electrostatic multipole effects that arise from the differences in charges on individual antibody domains. In three closely related studies, Kumar and coworkers 42,71,75 identified the molecular attributes that correlate with viscosity in highly concentrated antibody solutions, rationalized their observations using a putative mechanism involving antibody network formation gleaned from coarse-grained simulations, and then used this knowledge to rationally design viscosity reducing mutants of an antibody. They obtained concentration-dependent viscosity curves of eleven different antibodies under standardized formulation conditions, 71 and interpreted this experimental data in terms of sequence and structural attributes of the mAbs and their components.…”
Section: Strategies I and Ii: Effects Of Sequence And Structure Attrimentioning
confidence: 99%
See 2 more Smart Citations
“…9,15,[18][19][20] In addition to the multitude of distinct domain surfaces that can compose the binding interfaces, the nature of the driving forces behind antibody selfassociation can also be diverse, with both electrostatic and hydrophobic interactions playing key roles. 6,7,18,21,23 Potential strategies to mitigate self-association and other undesired high concentration solution properties may include protein engineering approaches, 20,[24][25][26] as well as formulation development and optimization efforts. [5][6][7]9,18,19,21,23,27 While the former can be limited due to the degree of knowledge of sites of interactions, the latter can be time and resource intensive and may not always be fully successful to a desired degree for all antibodies.…”
Section: Introductionmentioning
confidence: 99%